2010
DOI: 10.1074/jbc.m110.113092
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor γ Coactivator 1α or 1β Overexpression Inhibits Muscle Protein Degradation, Induction of Ubiquitin Ligases, and Disuse Atrophy

Abstract: Overexpression of the transcriptional coactivator peroxisome proliferator-activated receptor ␥ coactivator 1␣ (PGC-1␣), like exercise, increases mitochondrial content and inhibits muscle atrophy. To understand these actions, we tested whether PGC-1␣ or its close homolog, PGC-1␤, influences muscle protein turnover. In myotubes, overexpression of either coactivator increased protein content by decreasing overall protein degradation without altering protein synthesis rates. Elevated PGC-1␣ or PGC-1␤ also prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
197
2
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(221 citation statements)
references
References 71 publications
13
197
2
9
Order By: Relevance
“…Consistently, we have previously shown that a cluster of genes related to ribosomes and anabolic pathways is down-regulated in mTg skeletal muscle (32). Finally, in vitro, PGC-1α does not regulate the rate of protein synthesis in C 2 C 12 myotubes (14). As a consequence, the assessment of a wide range of parameters related to skeletal muscle hypertrophy revealed that the overall effect of SA was not different in mTg or mKO mice.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Consistently, we have previously shown that a cluster of genes related to ribosomes and anabolic pathways is down-regulated in mTg skeletal muscle (32). Finally, in vitro, PGC-1α does not regulate the rate of protein synthesis in C 2 C 12 myotubes (14). As a consequence, the assessment of a wide range of parameters related to skeletal muscle hypertrophy revealed that the overall effect of SA was not different in mTg or mKO mice.…”
Section: Discussionsupporting
confidence: 56%
“…The link between mTORC1 and skeletal muscle metabolism is thought to be PGC-1α (10,12). PGC-1α and PGC-1α4 positively modulate skeletal muscle mass under catabolic conditions (14,16,17). However, we have now found that regardless of mTORC1 activity, PGC-1α is not required for skeletal muscle remodeling via chronic overload.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In fact, oxidative stress and inflammation cause the expression of the peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha (PGC‐1α), a master regulator for mitochondrial biosynthesis, to be reduced and to an increase in autophagy, a mitochondria degradation system. Interestingly, Brault et al demonstrated that the overexpression of PGC‐1α caused a resistance to muscle atrophy that was induced by denervation or fasting 11. Similarly, Wenz et al also showed that the overexpression of PGC‐1α in mice prevented muscle atrophy and hence extended their life span 12.…”
Section: Introductionmentioning
confidence: 99%
“…While endurance exercise induces PGC-1 as described above different experimental or pathological muscle wasting conditions like denervation-induced atrophy, statin treatment, diabetes, uremia, and cancer cachexia, reduce PGC-1 and/or PGC-1 levels [138][139][140][141]. Accordingly, ectopic expression of PGC-1 or PGC-1 counteracts the atrophic state by suppressing atrogenes in vitro and in vivo [140][141][142]. PGC-1 coactivators are thus able to preserve muscle structure and function under unfavorable circumstances.…”
Section: Pgc-1 Coactivators In Skeletal Muscle Pathologymentioning
confidence: 99%